Basic mechanisms in endoplasmic reticulum stress and relation to cardiovascular diseases - SÖZEN, AHMET ERDİ; YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2015)
The folding process is an important step in protein synthesis for the functional shape or conformation of the protein. The endoplasmic reticulum (ER) is the main organelle for the correct folding procedure, which maintains the homeostasis of the organism. This process is normally well organized under unstressed conditions, whereas it may fail under oxidative and ER stress. The unfolded protein response (UPR) is a defense mechanism that removes the unfolded/misfolded proteins to prevent their accumulation, and two main degradation systems are involved in this defense, including the proteasome and autophagy. Cells decide which mechanism to use according to the type, severity, and duration of the stress. If the stress is too severe and in excess, the capacity of these degradation mechanisms, proteasomal degradation and autophagy, is not sufficient and the cell switches to apoptotic death. Because the accumulation of the improperly folded proteins leads to several diseases, it is important for the body to maintain this balance. Cardiovascular diseases are one of the important disorders related to failure of the UPR. Especially, protection mechanisms and the transition to apoptotic pathways have crucial roles in cardiac failure and should be highlighted in detailed studies to understand the mechanisms involved. This review is focused on the involvement of the proteasome, autophagy, and apoptosis in the UPR and the roles of these pathways in cardiovascular diseases. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Endoplasmic reticulum stress; Proteasome; Autophagy; Apoptosis; Cardiovascular diseases; Free radicals; UNFOLDED-PROTEIN RESPONSE; ACTIVATING TRANSCRIPTION FACTOR-6; ATTENUATES CARDIOMYOCYTE DEATH; UBIQUITIN-PROTEASOME SYSTEM; CARDIAC MYOCYTE APOPTOSIS; PANCREATIC BETA-CELL; ER STRESS; QUALITY-CONTROL; OXIDATIVE STRESS; MESSENGER-RNA